Synthesis and characterization of metal silicides nanostructures - Li, Shaozhou. (2013)
Metal silicides have been used extensively in microelectronics devices, such as contacts and local interconnects. With increasing research and development of a bottomup fabrication approach for semiconducting and metallic nanostructures, metal silicides nanostructures can continue to play an important role in the next generation of nanoelectronics. In this research, the crystallography and growth mechanism of several transition metal-silicide nanostructures grown on silicon substrates were investigated with the assistance of focus-ion beam (FIB) microscopy and transmission electron microscopy (TEM) analysis.